Material removal utilizing electrokinetic phenomenon on amorphous aluminium surfaces - Chua, Janet Min Chien. (2010)
To satisfy the global market demand in producing ever-smaller scales devices with higher dimensional accuracy and functional efficiency, material removal in nanometric level has become a huge interest and a great challenge. In order to have higher performance and reliability of miniaturized devices, there is a need to either improve the present machining techniques or develop novel material removal techniques for better machining capability.